P‐129: Operating Frequency and Sensitivity Prediction of In‐Display Ultrasonic Fingerprint Sensing Systems. Issue 1 (25th September 2020) - Park, Hyun Sung; Shin, Hyundo; Kim, Jisoo; Seo, Yudeok; Seo, Dongjin; Kim, Yongjo
Abstract : This work presents an operating frequency and sensitivity evaluation methodology for an ultrasonic fingerprint on display (FoD). Understanding the underlying physics of the complicated, highly coupled behavior of electromechanical sensors is indispensable for predicting the responses of ultrasonic waves in the multi‐layered system. And predicting the behavior of the ultrasonic waves in a multi‐layered display panel structure is critical for evaluating and optimizing its performance. In this work, we evaluated the optimal operating frequencies from Fabry‐erot resonance and represented acoustic pressure imaging at an operating frequency by developing the Finite Element Method (FEM) based numerical analysis models. This work allows engineers to predict behavior of devices, modify and optimize the designs efficiently